Critical Review of the Urgency of Strengthening the Implementation of Cyber Security and Resilience in Indonesia - Aulianisa, Sarah Safira; Indirwan, Indirwan (Lex Scientia Law Review, 2020)
The development of information technology in cyberspace is unavoidable. which followed by the vulnerability of threats and attacks on data and information traffic that can threaten the country's sovereignty. One of the ways that can be done is to strengthen Indonesia's cyberinfrastructure and institutions. The purpose of this legal research is to find out the urgency of regulating Cybersecurity and resilience in Indonesia and its challenges and obstacles, also to conduct a comparative study in several countries. This research is normative legal research with qualitative descriptive analysis. The results of the study indicate that arrangements regarding Cybersecurity and resilience are very important and must be enacted immediately.